In Vitro Culture Of Maize (Zea Mays L.) Inbred Line Sm5-4 - Nguyen, Thi Mai Anh (2005)
Tissue culture of inbred line SM5-4 maize (Zea mays L.), maternal parent of Putra J- 58 (F1 hybrids) was established using maize zygotic embryo as explant. To obtain embryogenic callus from mature and immature zygotic embryos of inbred line SM5- 4, manipulations of media components such as carbon, nitrogen, proline, and casein hydrolysate, and culture conditions such as incubation temperature, light, were carried out. Immature embryos have the ability to form callus and embryogenic calli, which can result in plant regeneration. At tissue culture level, the study aims at establishing the best tissue culture system via somatic embryogenesis and to overcome plant regeneration problems by manipulating the sucrose concentration, hormone combination and concentration, culture age, the type of medium formulation used to grow callus, incubation temperature, light and media formulation. Sterilization technique of maize from mature and immature maize seeds of the inbred line SM5-4 was investigated. Mature seeds (50 days old) and immature seeds (14 days after pollination) were disinfected by washing in different concentrations of sodium hypochlorite (Clorox) for different duration. Disinfection in 50%(v/v) Clorox solution (2.27% sodium hypochlorite) for 20 minutes gave 90% of contaminationfree culture of mature seeds whereas 50%(v/v) Clorox solution (2.27% sodium hypochlorite) for 15 minutes gave 75% of contamination-free culture of immature seeds. Reduction in Clorox concentration of 20% (v/v) Clorox (1.05% sodium hypochlorite) for 20 minutes gave high percentage (67%) of contamination- free culture of immature seeds that remain viable. N6 basal medium was found to be the best medium in enhancing both callus induction and embryogenic calli formation. The highest callus induction frequency on N6 basal medium supplemented with 9 pM 2,4-D from immature zygotic embryos was 79.5%. Both plants growth regulators, 2,4-D, IAA and BAP, kinetin, were capable of switching on the induction of callus necessary for embryogenic totipotency. The combination of 2,4-D and kinetin were however more effective in producing callus induction in embryos culture of maize. The most effective method for producing friable, embryogenic callus was found for immature zygotic embryos. Maturation of somatic embryos was enhanced by transferring the embryogenic callus after 4 weeks to medium containing 6% sucrose and Img/L NAA. During the following 3-4 weeks, as the somatic embryos developed, the cultures were transferred to the regeneration medium (MSO). Approximately 80% of immature zygotic embryos produced embryogenic callus and then plantlets. Immature embryos of inbred line SM5-4 produced the highest percentage of callus and showed the highest number of plant regeneration compared to mature zygotic embryos.